2013
DOI: 10.3171/2012.11.jns121243
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of deep vein thrombosis in 1277 consecutive neurosurgical patients undergoing routine weekly ultrasonography

Abstract: Object. Patients requiring neurosurgical intervention are known to be at increased risk for deep vein thrombosis (DVT) and attendant morbidity and mortality. Pulmonary embolism (PE) is the most catastrophic sequela of DVT and is the direct cause of death in 16% of all in-hospital mortalities. Protocols for DVT screening and early detection, as well as treatment paradigms to prevent PE in the acute postoperative period, are needed in neurosurgery. The authors analyzed the effectiveness of weekly lower-extremity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
1
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 32 publications
0
35
1
2
Order By: Relevance
“…Orthopedic and neurological surgery are known to be risk factors for VTE in the pediatric 26 and adult literature. 6,16,19 Our study found TBI-associated hospitalizations involving orthopedic surgery and cranial surgery, respectively, to be 2.4 and 1.8 times more likely to be complicated by VTE. Surgery and length of hospital stay may also be useful proxy indicators for severity of injury.…”
Section: Discussionmentioning
confidence: 63%
“…Orthopedic and neurological surgery are known to be risk factors for VTE in the pediatric 26 and adult literature. 6,16,19 Our study found TBI-associated hospitalizations involving orthopedic surgery and cranial surgery, respectively, to be 2.4 and 1.8 times more likely to be complicated by VTE. Surgery and length of hospital stay may also be useful proxy indicators for severity of injury.…”
Section: Discussionmentioning
confidence: 63%
“…These rates are higher than those reported for patients in a neurosurgical ICU. 14,16 In these studies, VTE screening was regimented and conducted on all patients; whereas in our study, VTE screening was performed only on patients with clinically suspected VTE. In addition, Goldstein et al 5 showed that the presence of an EVD was the only independent risk factor for a thromboembolic event among a cohort of neurological ICU patients.…”
Section: Discussionmentioning
confidence: 99%
“…18 A large retrospective review of patients in a neurological ICU determined that 86% of deep vein thromboses were detected by routine screening within the first week. 16 Early administration of chemical prophylaxis for these patients seems essential, but its use should be weighed against the potential risks for hemorrhagic complications.…”
mentioning
confidence: 99%
“…In addition to VTE risk, mortality rates have also been stratified with VTE prophylaxis in mind, and institution of DVT prophylaxis results in decreased mortality risk [3][4][5]. Multiple case reports and series on postoperative thromboembolic prophylaxis have been published, however clear guidelines for a "Best Practice" have yet to be described [6][7][8].…”
Section: Introductionmentioning
confidence: 99%